“The Gate of the Gods”, “the Gate of the Ancestors”, and “the Cosmic Balance” on Luristan's Bowl of the Iron age - najme amini; seyed saeed seyed ahmadi zavieh; iraj dadashi (هنرهای زیبا. هنرهای تجسمی)
This article discusses the mythological interpretation of celestial patterns found on a starry bowl from the Iron Age Lorestan culture. Due to the abstract designs of Lorestan Iron Age bronzes and the lack of written sources, the interpretation of mythological patterns on these bronzes has been based on personal interpretations of researchers. The hypothesis of this research is that the religion and rituals of the Lorestan culture are connected to astronomy and celestial phenomena, and interpreting the celestial patterns on Lorestan bronzes can provide insights into their religion and rituals. The article focuses on a starry bowl with celestial patterns and Aramaic inscriptions, previously interpreted within the context of ancient Semitic cultures, but now being interpreted based on Indo-Aryan religions and ancient Iranian textual sources. The study is descriptive-analytical and relies on data collected from museum and library sources. According to the research findings, two sections, 4(a) and 8, have been identified with Ursa minor and Ursa major constellations and are symbolic of the cosmic balance pans, resembling a cosmic scale. Section 4(b), which embodies the ring and staff symbols representing the “pater” grade in the Mithraic ritual, has been identified with the celestial forms of 'Tishtrya/ Mirzam'. This section is considered as a symbol of the 'Gate of the ancestors' (= Pitri-yāna). In contrast, section 8 of the bowl is identified with the celestial form of ' Ursa major' and is considered as a symbol of the 'Gate of the Demons' or Hell. However, the most significant part of the bowl, the celestial pole at the center of bowl, is a symbol of the 'Gate of the Gods' (= Dēva-yāna). Those who, through their connection to the great secrets, return to their centers and the center of existence can pass through the 'Gate of the Gods', and attain eternity and become one with the unique essence of God. From the 'Gate of the Ancestors', they either return to the material world or experience gradual liberation through the levels of the heavens. Those who pass through the 'Gate of the Demons' or Hell are the ones who have returned to the material world more than three times. We have identified the two four-winged stars of sections 4(a) and 8 with the stars Tishtrya (= alpha Canis Major) and 'Spica'. They are considered as symbols of the two guardian dogs of the Chinvat Bridge and the cosmic scale. It appears that in Iranian tradition, the responsibilities of guarding the 'Gate of the Gods' and the 'Gate of the Ancestors' were assigned to the two deities ‘Mithra’ and ‘keyvân’ (Saturn). Based on some evidence, The Lorestan bowl is engraved with symbols related to pre-Zoroastrian tradition. On this bowl, the concepts related to gates are associated with "polar symbolism", unlike the Indian tradition in which the "Gate of the Gods" were related to solar symbolism and the winter solstice.